Mechanisms and therapeutic strategies to reveal and overcome T-cell dysfunction in gastric cancer: translation from basic research to clinical application - Luo, Huanyu; Wu, Jianxi; Yan, Yalan; Xu, Danqi; Zhang, Jieying; Zhou, Xuancheng; Yang, Guanhu; Zhong, Xiaolin (Frontiers in Immunology, 2025)
T cells play a central role in the immune response to gastric cancer, and their dysfunction directly contributes to immune escape from the tumor and limits the efficacy of immunotherapy. The immune microenvironment of gastric cancer consists of a wide range of cells and molecules, and this complex and dynamic environment exerts profound inhibitory effects on T cell function. upregulation of PD-1, CTLA-4, and other inhibitory molecules is a key mechanism of T cell depletion, and metabolic reprogramming and chronic antigenic stimulation further weaken the anti-tumor activity of T cells. In recent years, PD-1/PD-L1 inhibitors have demonstrated some efficacy in gastric cancer, but the problem of drug resistance remains prominent. To address these challenges, combinatorial therapeutic strategies have gradually become the focus of research, especially combining immune checkpoint inhibitors with chemotherapy, radiotherapy, or targeted therapy to enhance the antitumor effect of immunotherapy. This review delves into the molecular mechanisms of T-cell depletion and its impact in gastric cancer immunotherapy, and analyzes the potential application of biomarkers in predicting treatment response. By comprehensively analyzing T-cell depletion and the immune microenvironment in gastric cancer, this paper provides a theoretical basis for the development of future personalized combinatorial therapeutic strategies, with the aim of improving patient prognosis and enhancing the overall therapeutic efficacy.